Field Evaluation of Different Fungicides Against Phoma Leaf Spot Disease of Indian Bean - V.A.PATIL; B.P. MEHTA; A.J. DESHMUKH (International Journal of Pharma and Bio Sciences, 2010)
A field experiment was laid out with the chemicals, which were found effective under laboratory screening to test relative field efficacy of different fungicides in controlling the Phoma leaf spot disease of Indian bean during summer season. Six fungicides at various concentrations were screened against Phoma tropica. The minimum per cent disease intensity (PDI) and maximum per cent disease control (PDC) was recorded in the field plots, which were sprayed with carbendazim (Bavistin 50 % WP@ 0.05%) and flusilazole (Nustar 40% EC @ 0.05%).